EMOTIONAL ECOLOGY AND ITS RELATION TO PERSONAL MARKETING - Vallejo Chávez, Luz Maribel; Jarrín Zambrano, Ginno Sidney; Tapia Bonifaz, Angelita Genoveva (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Emotional ecology offers a new, creative and revolutionary approach to emotional education by relating eco-emotions and personal marketing, helps to improve the new model of the human being: an emotionally ecological person. The research approach is qualitative, of an exploratory and descriptive level of documentary type for its theoretical foundation of the study, non-experimental and transversal design variables; The methods applied include the inductive, synthetic and systemic analytical deductive. It is concluded that the ecological-emotional approach based on the 4Rs focuses on the human being and their relationships in a way that is sustainable, in this sense: (i) reduce emotional pollutants found in the environment, the language we handle and surround ourselves of positive (non-toxic) people, (ii) recycle positive emotional resources, (iii) recover skills and abilities that everyone possesses and (iv) repair emotional wounds that produce a bagage of negative emotions that affect health and those around us . Emotional ecology becomes the art of sustainably managing our emotional world, the 4Rs being the basic rules that serve for cognitive and affective enrichment, and increasing the quality of good relationships, creating our own personal brand.